Overview of Self-Directed Learning Readiness (SDLR) in First-Year Nursing Students - Anggia Astuti Astuti; Dodi Wijaya; Zainal Abidin; Rizeki Dwi Fibriansari (KHD Production, 2024)
Self-directed learning (SDL) solves learning challenges using various learning tools. Nursing requires lifelong learning, and SDL is an important skill for practitioners to stay current and effective. It is required of nursing students to embrace SDL and hone these abilities. Nevertheless, there is no indication of this novel procedure in Lumajang. This study aims to assess nursing students' preparation for SDL and its impact on learning outcomes. This quasi-experimental study purposefully included 91 students who carry out basic nursing clinical practice as participants. The instrument used in this study was the Self-Directed Learning Readiness Scale (SDLRS) questionnaire developed by Fisher. The results of this study showed that there was an increase in the SDLR level from 9 students (9.9%) having a high SDLR level to 78 students (85.8%) and 82 students (90.1%) having a moderate SDLR level to 13 students (14.2%). The nursing students' average SDL preparedness level has a substantial impact on learning outcomes. Nursing training institutes should give the resources required to adopt SDL as a primary teaching technique to ensure competent lifelong professionals.